2004
DOI: 10.1038/nm1093
|View full text |Cite
|
Sign up to set email alerts
|

Specific recruitment of regulatory T cells in ovarian carcinoma fosters immune privilege and predicts reduced survival

Abstract: Regulatory T (T(reg)) cells mediate homeostatic peripheral tolerance by suppressing autoreactive T cells. Failure of host antitumor immunity may be caused by exaggerated suppression of tumor-associated antigen-reactive lymphocytes mediated by T(reg) cells; however, definitive evidence that T(reg) cells have an immunopathological role in human cancer is lacking. Here we show, in detailed studies of CD4(+)CD25(+)FOXP3(+) T(reg) cells in 104 individuals affected with ovarian carcinoma, that human tumor T(reg) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

148
3,850
32
39

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,483 publications
(4,131 citation statements)
references
References 45 publications
148
3,850
32
39
Order By: Relevance
“…However, macrophages are not the sole IL-10 source in tumors. Studies in human cancer have shown that Treg cells recruited at tumor sites produce abundant IL-10 [37,38], which may work as the main mediator of Treg-cell functional suppression [37]. Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, macrophages are not the sole IL-10 source in tumors. Studies in human cancer have shown that Treg cells recruited at tumor sites produce abundant IL-10 [37,38], which may work as the main mediator of Treg-cell functional suppression [37]. Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13].…”
Section: Discussionmentioning
confidence: 99%
“…Even with immune recognition of cancer, which can occur in cancer patients and is evidenced by the frequent observation of T cell infiltration into cancerous tissues [70][71][72][73], it is rare for such tumor infiltrating T cells to induce the spontaneous rejection of established tumors. Accumulating evidence indicates that the tumor environment contains cells and cytokines that actively suppress primed effector T cells [74,75].…”
Section: The Immunosuppressive Environment Inside Tumorsmentioning
confidence: 99%
“…Tregs play a key role in the prevention of T-cell responses to self-antigens. However, tumors can take advantage of Tregs by attracting them and manipulating Tregmediated immunosuppression in order to escape recognition and elimination by the host [20]. Their role in tumor progression is highlighted by the observation that systemic depletion of Tregs results in reduced tumor growth and increased survival in several models [21].…”
Section: Introductionmentioning
confidence: 99%